ANALISIS EFISIENSI PEMASARAN PINANG (Areca catechu L) DIKECAMATAN SAWANG - Dewi Alya; Saral Hasby Puarada; Ade Firmansyah Tanjung; Suryadi; Muhammad Authar ND (Jurnal Mahasiswa Agribisnis, 2025)
This research was conducted in Sawang District, North Aceh Regency, Riseh Tunong Village, Gunci Village, and Blang Teurakan Village. The samples taken were from the 3 villages as many as 20 farmers from Riseh Tunong Village, 15 farmers from Gunci Village and 13 farmers from Blang Teurakan Village. This study aims to 1) describe the general overview of areca nut marketing channels in Sawang District, North Aceh Regency. 2) analyze the efficiency of areca nut marketing in Sawang District, North Aceh Regency. The data used in this study is primary data obtained based on the results of observations and interviews conducted using questionnaires on sample farmers and traders and supported by secondary data from several literature. Based on the results of the research, it is known that areca nut marketing in Sawang District consists of 3 marketing channels, namely 1) channel I consists of farmers - wholesalers - end consumers/exporters, 2) channel II, namely farmers - collectors - final consumers/exporters, 3) channel III, namely farmers - collectors - wholesalers - end consumers/exporters. The results of the analysis of the most efficient marketing margin value are based on the size of the margin, namely channel I, which is Rp.2,800/Kg. the value of the farmer's share received by the largest farmer, namely in channel I, is 65% and the value of the profit-to-cost ratio in channel I Ï/C>1 is 3%.Keywords: Marketing Efficiency, Marketing Channel, Marketing Margin, Farmer's Share, Ï/C Ratio